Desenvolvimento de uma rede social na área de reparos residenciais - Silva, Daniel da (2016)
This Undergraduate Thesis presents the development of an evaluation social network in the field of facility maintenance. It allows service providers of a particular region to offer services in this area. Users can rate advertisements with a grade and comments that will be available to other people on the advertiser's profile. The project management was done using the Kanban method and the software development using Extreme Programming (XP) which is an agile development technique.